The Effects of Capital, Labor and Electricity Consumption on Economic Growth in Malaysia - Halim, Hamizah Abdul; Harun, Nor Hidayah; Shaari, Mohd Shahidan; Zainol Abidin, Noorazeela (International Journal of Energy Economics and Policy, 2020)
Capital and labour are common factors of production in boosting the economic growth. Apart from that, electricity consumption is a vital key to most industry sectors. However, there are very limited studies which consider this factor in the analysis particularly in Malaysia. Therefore, this study aims to investigate the effects of capital, labour and electricity consumption on economic growth in Malaysia using data period of 1982 to 2017. The autoregressive distributed lag bound testing approach was employed and the results reveal the significant effects of capital and electricity consumption on economic growth both in the short runs and the long runs. However, there is no significant effect of labour on economic growth in Malaysia for both short runs and long runs. The results may provide more understanding of prevalent factors of production that affects economic growth and can be a guideline for policy makers to boost the economic growth in Malaysia. Keywords: Capital, Labour, Electricity Consumption, Economic Growth, Autoregressive Distributed Lag JEL Classifications: O40, O44, Q4 DOI: https://doi.org/10.32479/ijeep.10034